Digital games based language learning for Arabic literacy remedial - Mohamed Masrop, Noor Azli; Ishak, Hafawati; Zainuddin, Ghazali; Ramlan, Siti Rosilawati; Sahrir, Muhammad Sabri (2019)
Digital game play is becoming increasingly prevalent. Its participant-players number in the millions and its revenues are in billions of dollars. As they grow in popularity, digital games are also growing in complexity, depth and sophistication. This paper presents reasons why games and gameplay matter to the future of education. Drawing upon these works, the potential for instruction in digital games is recognised. Previous works in the area were also analysed with respect to their theoretical findings. Hence, the authors in this study propose some existing Arabic language learning games intended for education of children. The analysis result shows that the majority of Arabic language learning games is limited to alphabet content. The overall presentation lacks of quality in term of graphics, animations, colors, and voice-over.